2018
DOI: 10.1038/s41598-018-35764-y
|View full text |Cite
|
Sign up to set email alerts
|

Increase of power conversion efficiency in dye-sensitized solar cells through ferroelectric substrate induced charge transport enhancement

Abstract: Ferroelectric functionalized dye-sensitized solar cells were fabricated by using a positively-poled LiNbO3 substrate coated with ITO (ITO-LiNbO3) as a collector electrode and demonstrated enhanced power conversion efficiency. Surface potential properties of TiO2 nanoparticle film coated on the ITO-LiNbO3 (TiO2/ITO-LiNbO3) examined by Kelvin probe force microscopy (KPFM) confirmed that a large electric field (a few 10 V/µm) generated from LiNbO3 can penetrate through the ITO layer and is applied to TiO2 film. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In the EIS measurement done under the dark condition and with an applied bias voltage, electrons from FTO are injected into the conduction band of ZnO and then transported through the ZnO network. Some of the injected electrons recombine with the I 3 − ion present in the electrolyte giving rise to the recombination phenomenon (Liu et al 2018). Figure 9(a)…”
Section: Electrochemical Impedance Spectroscopy Studymentioning
confidence: 99%
“…In the EIS measurement done under the dark condition and with an applied bias voltage, electrons from FTO are injected into the conduction band of ZnO and then transported through the ZnO network. Some of the injected electrons recombine with the I 3 − ion present in the electrolyte giving rise to the recombination phenomenon (Liu et al 2018). Figure 9(a)…”
Section: Electrochemical Impedance Spectroscopy Studymentioning
confidence: 99%
“…Due to the unique combination of physical and chemical properties, ferroelectric materials are widely used in the production of integrated optical devices, waveguide structures, phase modulators, piezoelectric transducers, and surface acoustic waves devices [12][13][14][15]. Besides, ferroelectric materials are promising for photoelectric converters due to their charging properties [16]. However, in most cases, piezoelectric films are based on multicomponent oxides (BaTiO 3 , SrTiO 3 , LiNbO 3 ), and their properties are determined by the stoichiometric composition and structure, which depend on the growth method and fabrication parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of implementing ferroelectric polarization to improve the performance of semiconductor devices through a polarization-induced internal field. For instance, ferroelectric LiNbO 3 and BaTiO 3 were employed to facilitate charge separation and transport in dye-sensitized solar cells to increase cell efficiency [15,16]. Recently, applications of ferroelectric polarization were also explored to enhance photocatalytic performance [17,18,19].…”
Section: Introductionmentioning
confidence: 99%